Urban cultural heritage is mentally restorative: an experimental study based on multiple psychophysiological measures - Wang, ShuSheng; Xu, Yuqian; Yang, Xinyi; Zhang, Yuan; Yan, Pei; Jiang, Yuan; Wang, Kai (Frontiers in Psychology, 2023)
Introduction Urban cultural heritage sites bear the cultural functions of a city, hold spiritual and cultural value, can recall emotional memories, and serve the cultural leisure activities of the residents. Urban cultural heritage sites can help citizens perceive a sense of belonging and a feeling of relaxation, but whether and to what extent cultural heritage sites affect mental health remains unknown. Methods Based on attention restoration theory, multiple research methods are adopted in this study to examine the impact of cultural heritage on human restorative mechanisms. Five representative cultural heritage sites from the cultural heritage-rich city of Xi'an are selected as the research object. In addition, a questionnaire survey and physiological experiments are conducted. Perceived restorative scale, skin conductance response, heart rate variability, and eye movement data while viewing photographs of the cases are collected from the participants. Results Results show that cultural heritage sites have psychophysiological restorative effects, which are especially significant in the fascination dimension. Moreover, historical buildings can promote the restorative effects of cultural heritage sites. Discussion This finding may lead to new conservation and innovation planning strategies considering the mental health effects of cultural heritage.